Pengaruh Pemberian Sarang Telur Laba-Laba (Spider Silk Protein) Menemerus Bivittatus Secara Topikal Terhadap Penyembuhan Luka Insisi Pada Fase Inflamasi Tikus Putih Jantan (Rattus Norvegicus) Strain Wistar - Muhammad Yusak Alfaris; Mas Mansyur (Universitas Wijaya Kusuma Surabaya, 2017)
The healing of wounds is a natural process of the human body but often medicine is used, for example the use of spider silk. The purpose of this research is to know the effect of the use of spider (Menemerus Bivittatus) silk protein used topically for the healing of incision wounds in the inflammatory phase. This research is a laboratory experiment. The subjects of this research are 18 wistar rats (Rattus Norvegicus strain) that are treated in two different ways. The first is control (K1) with the use of normal saline and the second is treatment (Pl) with the use of spider silk protein topically using wound dressing. The selection of samples is done randomly using the simple random sampling. The hypothesis testing uses the Chi Square testing with α = 0.05. The results of this research shows that the use of spider silk protein topically effects the process of incision wound healing (0,005) in the inflammatory phase (0,000) on Wistar rats.